First hybrid implantations of novel Salus-Valves in patients with severe pulmonary regurgitation: A case series - Shao, Zehua; Song, Shubo; Han, Yu; Liang, Weijie; Fan, Taibing (Frontiers in Cardiovascular Medicine, 2022)
With the increasing age of patients after right ventricular outflow tract (RVOT) reconstruction, progressive pulmonary valve (PV) dysfunction can result in different degrees of right heart insufficiency, and PV replacement is frequently needed during follow-up. The traditional redo thoracotomy is difficult and associated with higher risks when compared to transcatheter implantations. Herein, we report the advantages and describe the outcomes of the first hybrid implantations of the novel Salus-Valves (Balance Medical, Beijing, China) from the sub-xiphoid approach in 5 patients (mean age of 22.6 years) with severe pulmonary regurgitation (PR) after RVOT reconstruction.